2008
DOI: 10.1111/j.1439-0507.2008.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of dermatophyte onychomycosis with three pulses of terbinafine (500 mg day−1 for a week)

Abstract: We assessed the safety and efficacy of pulse therapy with terbinafine tablets in 55 patients with dermatophytic onychomycosis. One pulse consisted of oral terbinafine tablets (500 mg day(-1)) given for 1 week usually followed by a 3-week interval. This regimen was repeated twice. Topical 1% terbinafine cream was applied daily. Efficacy was assessed based on both clinical and mycological examinations 1 year after treatment initiation. We observed a complete cure in 41 patients (74.5%), marked improved in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…É um dos antifúngicos mais recomendados para o tratamento, sobretudo de onicomicoses, tanto para uso tópico, quanto oral, incluindo a pulsoterapia. 28 Enfim, este foi um estudo voltado exclusivamente aos microrganismos, mas que corrobora as constatações de autores que comprovam na clínica a eficácia do tratamento sistêmico com itraconazol, terbinafina e fluconazol, drogas consideradas de escolha na terapia de infecções fúngicas da pele e unhas. 29 Apesar disso, autores chamam a atenção para a necessidade da abordagem diferenciada em populações especiais, como idosos, crianças, gestantes e indiví-duos imunocomprometidos.…”
Section: Discussionunclassified
“…É um dos antifúngicos mais recomendados para o tratamento, sobretudo de onicomicoses, tanto para uso tópico, quanto oral, incluindo a pulsoterapia. 28 Enfim, este foi um estudo voltado exclusivamente aos microrganismos, mas que corrobora as constatações de autores que comprovam na clínica a eficácia do tratamento sistêmico com itraconazol, terbinafina e fluconazol, drogas consideradas de escolha na terapia de infecções fúngicas da pele e unhas. 29 Apesar disso, autores chamam a atenção para a necessidade da abordagem diferenciada em populações especiais, como idosos, crianças, gestantes e indiví-duos imunocomprometidos.…”
Section: Discussionunclassified
“…[32] A regimen of three weekly pulses of terbinafine (250 mg twice daily for 1 week every month) alone or in combination with topical terbinafine has also been found to be efficacious for dermatophyte onychomycosis. [33,34] Sikder et al, found 4 weekly pulses of terbinafine to be more effective than intermittent itraconazole. [35] Common adverse reactions with terbinafine include gastrointestinal symptoms, skin rash, pruritus, urticaria, asymptomatic liver enzyme abnormalities, and taste disturbances.…”
Section: Systemic Therapymentioning
confidence: 97%
“…127 As expected based on the comparative data generated from traditional dosing trials, the combination of pulse therapy with ancillary topical therapy does not substantially improve outcome over treatment with terbinafi ne alone. [126][127][128] In two comparative trials, terbinafine (250 mg/day) was significantly superior to griseofulvin (500 mg/day). Mycological cure rates were significantly higher with terbinafi ne (84%-92% vs 45%-63%), time to mycological cure significantly shorter (73 vs 93 days) and clinical cure significantly higher (76% vs 39%) as compared with griseofulvin.…”
Section: Onychomycosismentioning
confidence: 99%